The conventions of the International Labor Organization and domestic law (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The changes taking place in the dialogue between the international human rights protection system and Brazilian domestic law are also having a profound impact on the relationship between the international labor law system managed by the International Labor Organization (ILO) and the national legal system. Our aim is to analyze these reflections, taking into account the peculiarities of international labor law, whose system is the oldest among those for the protection of human rights.
Keywords: ILO; conventions; domestic law; ratification; conventionality control; jurisprudence